Legitimation and Delegitimation in Global Governance Practices, Justifications, and Audiences - Bexell, Magdalena; Jönsson, Kristina; Uhlin, Anders (Oxford University Press, 2022)
This book explores processes of legitimation and delegitimation of global governance institutions (GGIs). How, why, and with what impact on audiences, are GGIs legitimated and delegitimated? The book develops a comprehensive theoretical framework for studying processes of (de)legitimation in global governance and provides broad comparative analyses to uncover patterns of (de)legitimation processes. It covers a diverse set of global and regional governmental and nongovernmental institutions in different policy fields. Variation across these GGIs is explained with reference to institutional setup, policy field characteristics, and broader social structures, as well as to the qualities of agents of (de)legitimation. The approach builds on a mixed-methods research design that uses both quantitative and qualitative new empirical data. Three main interlinked elements of processes of legitimation and delegitimation are at the center of the analysis: the varied practices employed by different state and non-state agents that may boost or challenge the legitimacy of global governance institutions; the normative justifications that these agents draw on when engaging in legitimation and delegitimation practices; and the different audiences that may be impacted by legitimation and delegitimation. This results in a dynamic interplay between legitimation and delegitimation in contestation over the legitimacy of GGIs.